'A certain instability of mind': Herbert Mayo, 1796–1852, Surgeon and Physiologist. (May 2017) - Bradley, James
Herbert Mayo was a significant physiologist and an important figure in the London medical world of the 1820s and 1830s. And yet, a combination of poor decision-making and dabbling in heterodox medicine damaged his reputation. The life of Herbert Mayo illustrates that during the critical period before the 1858 Medical Act the boundary between orthodox and alternative medicine was porous. It also gives important insights into the politics of medicine at this time, particularly the significance of character to becoming a successful medical practitioner.